Análise dos mecanorreceptores e terminações nervosas livres do ligamento colateral lateral do cotovelo com imunofluorescência e microscopia confocal - Costa, Rafael Patrocínio de Paula (2024)
The Elbow Lateral Collateral Ligament(LCL) is an important static stabilizer against varus and posterolateral rotatory forces, being frequently injured in fracture or dislocations, resulting in articular instability and proprioception impairment. The purpose of this study is to describe the morphology and distribution of the LCL mechanoreceptors and free nerve endings. Twenty ligaments were obtained from 10 freshcadavers from Forensic Expertise ofCeará State (PEFOCE), in accordance with local legislation. Each ligament was measured, weighed and cut. The 10μm sections were prepared in hematoxylin-eosin (HE) stained slides in order to analyze tissue integrity, and the 50μm sections were subjected to immunofluorescence with the protein gene product (PGP) 9.5 as primary antibody and Alexa Fluor 488 as secondary antibody, followed by microscopic analysis (Zeiss® LMS 710). The LCL was identified in 100% of the dissections, showing average length36,2 ± 3,4mm,average width9,5 ± 2,24mm and average weight 0,8 ± 0,13g. Histological sections in HE showed dense and organized collagen fibers, in addition to the presence of vascular tissue. In all specimens analyzed, type I (Ruffini-like) and type IV (free nerve endings) mechanoreceptors were identified, ranging from parallel fibers to fibers in a coiled format. Unclassified nerve endings were also found, with diverse and irregular shapes. Thus, it was concluded that LCL has a peripheral nervous structure, primarily type I and IV mechanoreceptors. These findings suggest that LCL is important for proprioception and elbow stabilization.